2006
DOI: 10.1016/j.jtcvs.2005.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy to monitor cerebral oxygen saturation in single-ventricle physiology

Abstract: This study shows that in univentricular physiology cerebral oxygen saturation correlates well with jugular venous oxygen saturation, arterial oxygen saturation, and arterial oxygen content. However, our findings suggest that in singe-ventricle physiology changes in cerebral oxygen saturation need to be interpreted in the context of changes in arterial oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Others have tested the feasibility of NIRS to record changes in brain oxygenation induced by hypoxemia [15][16][17][18][34][35][36]. However, hypoxemia was induced by application of artificial gas-mixtures simulating high altitude hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have tested the feasibility of NIRS to record changes in brain oxygenation induced by hypoxemia [15][16][17][18][34][35][36]. However, hypoxemia was induced by application of artificial gas-mixtures simulating high altitude hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to SpO 2 , rSO 2 depends mainly on venous blood [14]. In previous methodological studies a clear positive correlation between SpO 2 and rSO 2 has already been demonstrated [16][17][18]. This correlation was shown in experiments where the participants inhaled hypoxic gas mixtures consisting of reduced O 2 substituted with N 2 during normocapnia.…”
Section: Introductionmentioning
confidence: 97%
“…It has the advantage of supplying a noninvasive, real-time, bedside measurement of cerebral oxygenation and hemodynamics which can be critical for the medical team to initiate interventions to maintain a safe cerebral oxygenation level. 10,14 The purpose of this study is to assess the performance of noninvasive NIRS monitoring and hemodynamic variables as predictors of survival and NDO in neonates with CHD undergoing cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing rSO 2 values are thought to reflect shifts in the delicate balance between cerebral O 2 supply and demand, suggestive of cerebral hypoxia; and indicate the need for interventions aimed at improving cerebral perfusion 33,53 . Similarly, keeping rSO 2 values ≥ 75% of the pre-induction baseline value has been associated with a decreased incidence of post-operative neurological outcomes and shorter hospital stays 12,33 .…”
Section: Discussionmentioning
confidence: 99%
“…By measuring the concentrations of oxygenated haemoglobin (oxyHb) and deoxygenated haemoglobin (deoxyHb), regional cerebral oxygen saturation (rSO 2 ) is determined 37,52,53 . An rSO 2 value greater than 20% below the baseline is indicative of cerebral hypoperfusion and should prompt immediate intervention to improve cerebral oxygenation, and thus prevent cerebral injury 8,12,13,36,51,53 .…”
Section: Non-invasive Neuromonitoringmentioning
confidence: 99%